Detailed understanding of reduced geoeffectiveness of solar cycle 24 in association with geomagnetic storms - R. Selvakumaran; Sneha A. Gokani; Shirsh Lata Soni (Frontiers in Astronomy and Space Sciences)
Solar Cycle 24, the weakest in over a century, exhibited significant deviations from previous cycles, beginning with a prolonged minimum, weak polar fields, and asynchronous polar field reversal, leading to hemispheric asymmetry. Sunspot activity declined by approximately 30% compared to Cycle 23, while the overall occurrence rate of coronal mass ejections (CMEs) decreased, although some studies suggest that the rate of halo CMEs relative to total CMEs may have remained relatively stable. This study investigates the impact of weaker solar activity on geomagnetic storm dynamics by analyzing CME properties, solar wind conditions, and their influence on magnetospheric energy transfer. Key findings indicate that a lower heliospheric pressure in Cycle 24 caused CMEs to expand more than in Cycle 23, altering energy transfer to Earth’s magnetosphere. Despite the reduced overall CME rate, the weaker interplanetary magnetic field (IMF) and solar wind pressure led to an 80% reduction in intense geomagnetic storms and a 40% reduction in moderate storms. A detailed epoch analysis revealed a significant delay in the magnetospheric response in Cycle 24 compared to Cycle 23, highlighting the role of weakened solar wind forcing. Furthermore, analysis of the Perrault-Akasofu coupling function (ε) showed that the pressure-corrected energy transfer parameter (ε**) provides a more accurate estimate of magnetospheric energy input. These findings highlight how reduced heliospheric pressure and weaker solar wind conditions during Solar Cycle 24 significantly influenced geomagnetic storm activity by altering CME expansion and energy transfer to the Earth’s magnetosphere, thereby enhancing our understanding of solar-terrestrial coupling processes and improving the predictive capability of space weather models.